2017
DOI: 10.1172/jci.insight.90111
|View full text |Cite
|
Sign up to set email alerts
|

Btk-specific inhibition blocks pathogenic plasma cell signatures and myeloid cell–associated damage in IFNα-driven lupus nephritis

Abstract: Systemic lupus erythematosus (SLE) is often associated with exaggerated B cell activation promoting plasma cell generation, immune-complex deposition in the kidney, renal infiltration of myeloid cells, and glomerular nephritis. Type-I IFNs amplify these autoimmune processes and promote severe disease. Bruton's tyrosine kinase (Btk) inhibitors are considered novel therapies for SLE. We describe the characterization of a highly selective reversible Btk inhibitor, G-744. G-744 is efficacious, and superior to bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 57 publications
3
59
0
Order By: Relevance
“…Autoantibodies can then deposit in the kidney, activating local cells, including macrophages, via Fc receptors. These activated cells initiate a localized inflammatory immune response which damages the kidney, leading to renal disease [16]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autoantibodies can then deposit in the kidney, activating local cells, including macrophages, via Fc receptors. These activated cells initiate a localized inflammatory immune response which damages the kidney, leading to renal disease [16]. …”
Section: Discussionmentioning
confidence: 99%
“…A separate study by Katewa et al examined BTK inhibition in an alpha-IFN accelerated model in NZB/W mice, with a reduction in plasmablasts, autoantibodies, and renal disease [16]. Finally, Kim et al recently reported beneficial effects of HM71224, a selective BTK inhibitor, on renal disease and mortality when given prophylactically in NZB/W and MRL/lpr mice[19].…”
Section: Discussionmentioning
confidence: 99%
“…53 Btk is a nonreceptor tyrosine kinase that is a promising target for treating diseases caused by B cell dysregulation, such as B-cell malignancies and autoimmune diseases including rheumatoid arthritis and lupus. 5458 CC-292 53 as well as drugs such as ibrutinib 59 contain an acrylamide electrophile that reacts with a conserved Cys (481) in the Btk active site. We synthesized a fluorescent probe based on CC-292 that was used to quantify levels of Btk engagement by CC-292 both in cell culture (Ramos cells) as well as in B lymphocytes obtained from rats dosed with CC-292.…”
Section: In Vivo Target Vulnerability: Chemical Tools To Quantify Tarmentioning
confidence: 99%
“…Specific Btk inhibitor treatment of NZB/W F1 mice ameliorated lupus‐like disease by reversing the accumulation of germinal center and plasma B cells and lowering anti‐dsDNA autoantibodies levels . Improved glomerular pathology and function were also observed after Btk inhibition . In an inducible model of lupus nephritis, Btk inhibition decreased complement deposition in the kidneys and reduced inflammatory cytokine production .…”
Section: The X Chromosome In Autoimmunitymentioning
confidence: 97%
“…SLE is a disease often characterized by excessive B cell activity, which results in increased production of cytokines and autoantibodies that elevate inflammation and cause organ damage . Specific Btk inhibitor treatment of NZB/W F1 mice ameliorated lupus‐like disease by reversing the accumulation of germinal center and plasma B cells and lowering anti‐dsDNA autoantibodies levels . Improved glomerular pathology and function were also observed after Btk inhibition .…”
Section: The X Chromosome In Autoimmunitymentioning
confidence: 99%